Early 20th Century Examples of Stakeholder Reporting from U.S. Corporate Annual Reports - Kevin Feeney (Journal of Social and Development Sciences, 2012)
The content of traditional annual reports for publicly owned corporations is undergoing significant change. Whether in the traditional printed form, or increasingly, via web-based formats, annual reports are moving beyond the mere reporting of the fiscal year’s financial results. Corporate annual reports are beginning to include supplemental disclosures on the corporation’s labor and supplier activities environmental activities, governance, social responsibility and, most recently, sustainability. This trend has been observed more frequently for corporations based outside of the United States, though a small number of U.S corporations have embraced these concepts as well. Such supplemental disclosures are made not only to its shareholders, but also to individuals, groups and other entities that have a direct stake (i.e. stakeholders) in the corporation’s activities, successes and/or other matters at hand. This paper looks at the development of the stakeholder model and some of groups involved in the expansion of annual reports to include their concerns. Looking back historically, the paper examines early examples of stakeholder reporting from 20th Century annual reports of Ford Motor Company and by certain publicly owned U.S. railroads. Lastly, the paper provides evidence of an earlier example of stakeholder reporting then that previously identified in the literature.